Butoh, as heard by a dancer / Dominique Savitri Bonarjee. - Bonarjee, Dominique Savitri (Routledge advances in theatre & performance studies., 2024)
This volume explores the origins of Butoh in postwar Japan through orality and transmission, in conjunction with an embodied research approach.